2022
DOI: 10.1073/pnas.2118697119
|View full text |Cite
|
Sign up to set email alerts
|

A predictive microfluidic model of human glioblastoma to assess trafficking of blood–brain barrier-penetrant nanoparticles

Abstract: Significance The blood–brain barrier represents a major therapeutic challenge for the treatment of glioblastoma, and there is an unmet need for in vitro models that recapitulate human biology and are predictive of in vivo response. Here, we present a microfluidic model of vascularized glioblastoma featuring a tumor spheroid in direct contact with self-assembled vascular networks comprising human endothelial cells, astrocytes, and pericytes. This model was designed to accelerate the development of tar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 94 publications
0
63
1
1
Order By: Relevance
“…Human BBB models are of great interest to the scientific community and pharma industries for testing drug transport across microvessels in a 3D microenvironment with close similarity to the in vivo human brain microvasculature [29]. Advanced microphysiological models using microfluidic technology have demonstrated the potential to accelerate in vitro pre-clinical validation and screening of novel drugs and their nanovectors for effective therapeutic treatments [30,32]. Such systems are expected to facilitate a more comprehensive comparison among different drug candidates for an accurate preclinical assessment of their ability to cross the human BBB (figures 2(e) and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Human BBB models are of great interest to the scientific community and pharma industries for testing drug transport across microvessels in a 3D microenvironment with close similarity to the in vivo human brain microvasculature [29]. Advanced microphysiological models using microfluidic technology have demonstrated the potential to accelerate in vitro pre-clinical validation and screening of novel drugs and their nanovectors for effective therapeutic treatments [30,32]. Such systems are expected to facilitate a more comprehensive comparison among different drug candidates for an accurate preclinical assessment of their ability to cross the human BBB (figures 2(e) and 3).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the treatment of 3D GBM culture causes a notable reduction of tumor size, in line with a considerable decrease in cell viability, demonstrating a marked inhibition of tumor growth. To mimic the BBB–GBM interaction in vitro, Straehla JP et al [ 120 ] designed a microfluidic device of vascularized GBM using GBM spheroids, derived from the co-culture of the patient-derived xenograft (PDX) GBM22 cell line with pericytes (PCs), in direct contact with a self-assembled and perfusable vascular network made of induced pluripotent stem cells (IPS), human endothelial cells, astrocytes and pericytes. In this model, GBM spheroids grew rapidly in close contact with their surrounding BBB vasculature, similar to what can be observed in vivo in HGG patients and in animal models of GBM.…”
Section: Advanced Pre-clinical Models To Study Nps In Pediatric Brain...mentioning
confidence: 99%
“…7 Straehla et al reported a self-assembled vascularized μBBB + GBM system to test the BBB permeability and GBM-targeting ability of surface-functionalized nanomedicines. 118 This model closely represents the real tumor vasculature and is suitable for the study of BBB transition to the BTB. The BBB permeability of nanomedicines can be quantified by monitoring the fluorescence intensity change of the labeled drug at different time points in the extravascular gel compartment.…”
Section: Lab On a Chip Critical Reviewmentioning
confidence: 99%